Description of the immature stages of Larinus vulpes and notes on its biology (Coleoptera, Curculionidae, Lixinae) - Skuhrovec, Jiří; Volovnik, Semyon; Gosik, Rafał (ZooKeys, 2017)
Mature larva and pupa of Larinus vulpes (Olivier, 1807) (Curculionidae: Lixinae: Lixini) are morphologically described for the first time and compared with known larvae and pupae of other Larinus species. Very high counts of larval body setae (pronotum with more than 25 setae and postdorsum on meso- and metathorax and also on abdominal segments I-VII with more than 12 setae) are characteristic features of the nominotypical subgenus Larinus. The biology of the species was studied in Ukraine. Echinops ruthenicus and E. sphaerocephalus were identified as host plants of both larvae and adults of this weevil based on the present research in Ukraine, which shows probably oligophagous. Overwintering beetles emerged at the end of May or earlier, then feeding and mating on the host plants. The highest level of adult activity was observed at the end of June. Larvae were endophagous within the flower heads. In July and August, the larvae pupated within inflorescences in a pupation cell. Adults exited the cells at the end of August and did not hibernate on the host plants. Sometimes, larvae and imagines of a new generation were found outside the flower heads in chambers constructed on the stems.
Keywords: Echinops; host plant; life history; Palaearctic Region; weevil; eastern Europe; Asteraceae; larva; larval development; pupa; morphology